A SURVEY ON THE IMPORTANCE OF PUBLIC-PRIVATE PARTNERSHIP PROGRAM IN MALAYSIA: PUBLIC PRACTITIONERS' PERSPECTIVE (Journal of Economics and Sustainability, 2023)
This study aims to determine the importance of Public-Private Partnership (PPP) programs as perceived by public practitioners in Malaysia. Other than that, we examine the differences in perceptions between groups of public practitioners, particularly from the PPP unit, the Ministry of Finance (MOF), and implementing ministries/agencies pertaining to the same matter. The study also explores public practitioners' opinions on the program's weaknesses and possible improvements for future undertakings. A questionnaire survey was utilised to elicit the perceptions of public practitioners concerning the importance of the PPP programme. Here, 106 usable responses were obtained and analysed using the Statistical Package for Social Sciences (SPSS) to rank the programme’s important rationale. Subsequently, it examines the differences in perceptions between groups through descriptive statistics, mean scores, and Kruskal-Wallis test analysis. Subjective responses have also been elicited to obtain respondents’ input on the weaknesses of the PPP programme and suggestions for future improvement. The results reveal that the crucial reason for PPP is to enhance private sector participation in economic development. Furthermore, overall responses suggest that every 14-rationale inquiry is either moderately important, important, or strongly important, with reasons relating to economic growth and development becoming the leading objective for PPP. Apart from that, the findings indicate no significant differences in perception among groups of respondents in the public sector. For the subjective responses, some respondents have highlighted many valuable inputs, and some require further qualitative research to analyse the issue independently.